Embedding Sustainability Competencies Through SULAM: Evidence from Hospitality and Tourism Education - Adie Effendi Zulkeflli; Muhammad Azizan; Aida Khalida Mohamed Idris (Management Institute Faculty of Economics Universitas Andalas, 2026)
Service-Learning Malaysia - University for Society (SULAM) has emerged as a transformative pedagogical approach in Malaysian higher education, fostering meaningful integration between academic learning and community engagement. Within hospitality and tourism education, SULAM provides a platform for embedding sustainability values through experiential practice. This study evaluates the learning outcomes of a SULAM-based community project involving undergraduate students from the Faculty of Hotel and Tourism Management at Universiti Teknologi MARA Pulau Pinang. Data were collected from 42 students through a structured questionnaire assessing four domains: understanding of SULAM objectives, interpersonal competence, leadership development, and civic engagement intention. Findings indicate consistently high levels of agreement across all constructs. More than 90% of respondents demonstrated a clear understanding of programme objectives and the ability to apply academic knowledge in real-world community settings. Students reported notable improvements in communication skills, teamwork, and engagement with diverse stakeholders. Leadership development was also evident, particularly in initiative-taking and responsibility management. Notably, 97.6% expressed willingness to participate in future SULAM initiatives. These findings affirm SULAM as an effective experiential learning model that promotes sustainability-oriented mindsets and supports socially responsible education in hospitality and tourism.